2013
DOI: 10.1371/journal.pone.0067458
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inactivation of EFEMP1 Is Associated with Tumor Suppressive Function in Endometrial Carcinoma

Abstract: ObjectiveEFEMP1, the epidermal growth factor–containing fibulin-like extracellular matrix protein 1, functions as an oncogene or a tumor suppressor depending on the cancer types. In this study, we aim to determine whether EFEMP1 affects the tumorigenesis and progression of endometrial carcinoma.MethodsThe expression of EFEMP1 was investigated using immunohistochemistry in a panel of normal endometrium (n = 40), atypical hyperplasia (n = 10) and endometrial carcinoma tissues (n = 84). Methylation status of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
(39 reference statements)
4
37
0
Order By: Relevance
“…Sadr-Nabavi et al determined a similar outcome in sporadic breast cancer using RNA microarray expression analyses (10). Of note, our findings also correlate with demonstrations of EFEMP1 downregulation reported in instances of endometrial cancer by Yang et al (18). According to this study, the decrease in EFEMP1 expression is mainly regulated by promoter hypermethylation, a finding consistent with our preliminary results that suggest differential methylation patterns in leiomyomata.…”
Section: Discussionsupporting
confidence: 92%
“…Sadr-Nabavi et al determined a similar outcome in sporadic breast cancer using RNA microarray expression analyses (10). Of note, our findings also correlate with demonstrations of EFEMP1 downregulation reported in instances of endometrial cancer by Yang et al (18). According to this study, the decrease in EFEMP1 expression is mainly regulated by promoter hypermethylation, a finding consistent with our preliminary results that suggest differential methylation patterns in leiomyomata.…”
Section: Discussionsupporting
confidence: 92%
“…EFEMP1 abrogated angiogenic activities and sprouting in MB114 cells by decreasing the expression of MMP-2 and MMP-3 (13). EFEMP1 is associated with decreased MMP-2 and MMP-7 levels in lung cancer (14) and MMP-2 and MMP-9 levels in endometrial carcinoma (15), which are somewhat similar to our data. We found that downregulation of EFEMP1 increased the expression of MMP2 and MMP9, and MMP2 and MMP9 level in clinical samples showed the same tendency: the lower the EFEMP1 the higher the MMP2 and MMP9 expression was.…”
Section: Discussionsupporting
confidence: 90%
“…The primers for amplification of IL‐6, total aromatase mRNA and aromatase promoter I.3, I.4, I.7 and II mRNA are shown in the Supporting Information. RNA extraction, real‐time RT‐PCR and western blot were performed as described previously . IHC was performed as described previously and evaluation of aromatase and IL‐6 staining was performed based on staining intensity proportion scoring systems used for breast carcinoma tissues (See Supporting Information).…”
Section: Coculture Experimentsmentioning
confidence: 99%